Die herstandaardisering van Afrikaans : 'n praktiese benadering met die AWS as gevallestudie - Odendaal, Beatrix Gertruida (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: This study comprises an investigation into the restandardisation of Afrikaans. Since the 1980s, there have been various calls from the Afrikaans speech community for the democratisation of Afrikaans by making it representative of the whole Afrikaans speech community. Despite these calls for the restandardisation of Afrikaans, a matter which has been brought to the fore in recent years, there are still no real theoretically-based and practical suggestions for such a project. The practical approach to the restandardisation of Afrikaans suggested in this study, with a specific focus on the restandardisation of the orthography of Afrikaans, informs the suggestion of a model by which such a planned restandardisation programme for Afrikaans could be carried out. This is done based on existing theories of standardisation and restandardisation, as well as a thorough investigation into the history of the standardisation of Afrikaans in order to determine the reasons underlying this need for its restandardisation. Firstly, relevant theories of standardisation are considered in order to determine which aspects of language standardisation give rise to restandardisation and play the most important role in it. The history of the standardisation of Afrikaans is also considered, in order to indicate the factors which gave rise to the calls for the restandardisation of Afrikaans. The world-wide phenomenon of destandardisation – an increasing trend by which the validity of standardised languages is called into question – is subsequently considered. Following this, restandardisation is considered in greater detail. Although the term is used widely, there are not yet thorough theoretical descriptions of the nature of the process itself. Therefore, this study provides a theoretical consideration of what restandardisation comprises. An investigation into various examples of attempts at the restandardisation of languages in South Africa, Africa, and the rest of the world serves as a backdrop against which the need for the restandardisation of Afrikaans is discussed. The standardisation of the orthography of Afrikaans, as outlined in the ten issues of the Afrikaanse woordelys en spelreëls (“Afrikaans word list and spelling rules”) which have been published to date, is the next research focus. The purpose of this critical evaluation of the primary source for orthographic standardisation of Afrikaans is to point out the weaknesses in the current standardisation process which necessitate a new approach to the standardisation of Afrikaans (and by extension, its restandardisation). Finally, a model is presented for the restandardisation of the orthography of Afrikaans, but also Afrikaans as a whole, based on various theoretical and practical considerations contained in the study.